Kontribusi Pelatihan Kerja, Kompensasi Finansial dan Pengembangan Karir terhadap Kinerja Tenaga Pendidik di Yayasan Perguruan Sultan Iskandar Muda - Robert Ruslim; Hendra Nazmi; Lulu Syahwitri; Michael Michael; Sri Puspa Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of training, compensation, and career development on teacher performance at SMA Yayasan Sultan Iskandar Muda Medan. The research method used is quantitative with a multiple linear regression analysis approach. The data used consists of primary and secondary data, and is analyzed using SPSS software. The results of the study indicate that all independent variables meet the classical assumptions, including normality, multicollinearity, and heteroscedasticity. Multiple linear regression tests show that training has a positive and significant effect on teacher performance with a significance value of 0.001. Compensation also has a positive and significant effect on teacher performance with a significance value of 0.006. Career development also has a positive and significant effect on teacher performance with a significance value of 0.007. Simultaneously, the results of the F test show that training, compensation, and career development together have a significant effect on teacher performance with a significance value of 0.000. The conclusion is that increasing training, compensation, and career development contributes to improving teacher performance at SMA Yayasan Sultan Iskandar Muda Medan. The implications of this study can be a basis for policy makers in improving the quality of educators through effective human resource management strategies. Keywords: Job Training, Financial Compensation, Career Development, Performance